Pengaruh Pendapatan Daerah, Belanja Daerah, Dan Surplus/Defisit Laporan Keuangan Pada Ketahanan Fiskal Pemerintah - Cynthia Febrianti; I Gde Sudi Adnyana (Jurnal Ilmiah Akuntansi Kesatuan, 2022)
Fiscal autonomy or fiscal decentralization is a local government can manage the finances of regions whose financial resources become the authority of the local government. To maintain fiscal sustainability there are several preventive measures that can be taken to minimize risks and maximize the productivity of the State Budget. The purpose of this study is to find out whether regional revenues, regional expenditures and surplus/deficit of financial statements affect the fiscal resilience of districts and cities in Indonesia in 2016-2018 The sample from this study is secondary data obtained from the Financial Examiner's Board by sampling method of Probabiliy Sampling and Stratified Random Sampling. The study was tested using EVIEWS. It found that regional spending and surplus/deficit financial statements had a significant influence on regional fikasl resilience, while regional revenues did not affect significantly. Keywords: Revenue, Expenditure, Surplus/Deficit, Fiscal Resilience.